“They Behave Like Jews”: Anti-Speculation Propaganda and the Creation of a Caste of “New Traders” in Lithuania in 1941–1944 - Indrišionis, Darius (Genocidas ir rezistencija, 2024)
The article analyses socio-economic propaganda campaigns that were actively developed in the Lithuanian press during the period from 1941 to 1944: 1) anti-speculation propaganda; 2) calls for Lithuanians to engage in trading (this can be visually called the creation of a cast of “new traders”). In 1941, after the occupation of Lithuania by Nazi Germany, speculative activities increased due to the difficult economic situation, the faltering supply of food products to cities and the interruption of the supply of industrial goods (for example, kerosene, textiles) to villages. The occupation regime carried out an active anti-speculation propaganda campaign, which manifested itself in three ways: 1) calls not to buy goods from speculators and to report speculators to the authorities; 2) promoting legal alternatives to speculation (such as commissions or barter stores); 3) intimidation through repression. The creation of the caste of “new traders” was based on the belief that Lithuanians would willingly take advantage of the Holocaust, when Jewish traders who had held significant positions in pre-war Lithuanian trade, especially in the private sector, were killed (or isolated in ghettos) along with the Jewish community. Lithuanians were urged through the press to engage in trade business, to create a new, nationally socially oriented, qualitatively different trade system. The network of trade schools had been actively expanded in the towns of the provincial regions. Despite their ambitions, these two propaganda campaigns did not achieve their goals. Speculation was active throughout the war, while its legal alternatives were unattractive and unpopular, and the actual practice of punishing speculators was far more moderate than the press calls for the death penalty. The creation of the “new traders” caste was also unsuccessful: although trade schools soon began to prepare new trade sector employees, relatively few were prepared, and the same press soon began to criticize “new traders” for taking over “Jewish speculation” and for tending to deceive buyers and the regime.